Applications of Artificial Intelligence in the Food and Beverage Industry - Prefa, Chinyere Ada; Omoregie, Lovelyn Chigozirim; Eze, Precious (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
For us to survive and be healthy, food safety is essential. In order to protect consumers from food-borne illness and reduce the likelihood that food companies will incur millions of dollars in recall costs and possible harm to their brand, the complexity and sophistication of today's food systems require adhering to the strictest food safety regulations and utilizing cutting-edge technologies. The theory and development of computer systems capable of carrying out tasks that typically require human intelligence is known as artificial intelligence (AI). In an effort to increase profits and find new ways to reach and serve customers, the food industry has started to adopt AI technologies due to intense competition and rising demand. Applications like fresh produce sorting, supply chain management, food safety compliance monitoring, efficient cleaning in place systems, predicting consumer preferences, and new product development with increased efficiency and time and resource savings have all been successfully implemented with AI. Adoption of AI technologies is hampered by a number of factors, such as cost, cultural shifts, the need for specialized knowledge, problems with transparency, and one-track minds. Research on AI-optimized production processes is still ongoing despite these obstacles, but it's crucial to remember that the advantages of using AI in the food industry far outweigh the drawbacks.